Alcohol Problems In Native America: the Untold Story Of Resistance And Recovery "The Truth About The Lie" - Coyhis D. L.; Coyhis Don L.; White William L. (Colorado Springs White Bison Inc., 2006)
The Idea of colonialism is far from the past as Indigenous people are barely coming to a better understanding of what this means. The book "Alcohol Problems in Native America" is a breath- taking book about this chemical weapon (alcohol) and other substances that take life out of our communities/Nations and thus we need to create a school of knowledge for our free,prior and informed consent as regards to the right to practice and revitalize our (Indigenous) traditions and customs. This is the first step to the many steps that we a First peoples need to act on to be free. A need to read for everyone to combat myths and distortions of history and its impact on our collective communities.
Keywords: 94(73)